2015
DOI: 10.1021/acs.orglett.5b01461
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Substituted Benzenes via Bi(OTf)3-Mediated Intramolecular Carbonyl Allylation of α-Prenyl or α-Geranyl β-Arylketosulfones

Abstract: Intramolecular carbonyl allylation of α-prenyl or α-geranyl β-arylketosulfones 5 in the presence of molecule sieves (MS) affords substituted benzenes 6-7 in moderate to good yields. The facile transformation proceeds by a synthetic sequence starting with the α-prenylation or α-geranylation of 1 and the Bi(OTf)3-mediated annulation of 5 followed by a sequential desulfonative aromatization or then an intramolecular Friedel-Crafts alkylation. A plausible mechanism has been studied and proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 66 publications
(19 reference statements)
1
14
0
Order By: Relevance
“…When aryl ketone 11 was converted using catalytic amounts of Fe(OTf) 3 , the corresponding tetrahydronaphthalene 12 was obtained in 23% yield with full conversion of the substrate (entry 1, Table 1). The use of Bi(OTf) 3 10 resulted in increased yields of 48% while catalytic quantities of GaCl 3 further improved the yield of 12 to 58% (entries 2 and 3, Table 1). Both, SnCl 4 and BF 3 ·Et 2 O resulted in the formation of tetrahydronaphthalene 12 in comparable yields of 87% while AlCl 3 , a more potent Lewis acid, formed 12 in diminished yields of 73% (entries 4–6, Table 1).…”
mentioning
confidence: 99%
“…When aryl ketone 11 was converted using catalytic amounts of Fe(OTf) 3 , the corresponding tetrahydronaphthalene 12 was obtained in 23% yield with full conversion of the substrate (entry 1, Table 1). The use of Bi(OTf) 3 10 resulted in increased yields of 48% while catalytic quantities of GaCl 3 further improved the yield of 12 to 58% (entries 2 and 3, Table 1). Both, SnCl 4 and BF 3 ·Et 2 O resulted in the formation of tetrahydronaphthalene 12 in comparable yields of 87% while AlCl 3 , a more potent Lewis acid, formed 12 in diminished yields of 73% (entries 4–6, Table 1).…”
mentioning
confidence: 99%
“…Subsequent screening of solvents showed that the use of other common solvents, such as chloroform, 1,2-dichloroethane, or toluene, did not improve the yield (entries 1-4). Replacement of the phenyl group adjacent to nitrogen of 1a by 4-chlorophenyl (1a-Cl), p-tolyl (1a-Me) and 4-methoxyphenyl (1a-OMe) groups, respectively, gave slightly different yields (entries [5][6][7]. Thus the following reaction conditions were chosen for all subsequent reactions: 0.2 mmol of 1 (1-OMe in some cases), 0.24 mmol of acetyl bromide and 2 mL of dichloromethane were stirred at room temperature under N 2 atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…First, addition of acetyl bromide to 1a produces propargylic acetyliminium/amidoallenylium A, which undergoes the first cyclization to give eneallene intermediate B. [5] The intermediate B experiences a 1,5-H shift offering triene intermediate C, [6] in which a 6p-electrocyclization occurs to achieve the second ring closure and generate D. [6a, b, 7] The elimination of a molecule of acetanilide finishes the last aromatization to produce 2a (Scheme 5).…”
Section: Resultsmentioning
confidence: 99%
“…Among bismuth(III) salts, [25–27] Bi(OTf) 3 belongs to a group of efficient and environmentally benign promoters for catalysing various functional group transformations and establishing carbon‐carbon/carbon‐heteroatom bond formations. In continuation of the recent research on a diverse set of Bi(OTf) 3 ‐promoted reactions [28–31] and the related synthetic applications of α‐sulfonyl o ‐hydroxyacetophenones, [32–33] we present a Bi(OTf) 3 ‐mediated one‐pot (4+1) annulation route (called the Rap‐Stoermer reaction) to 3‐sulfonylmethyl 2‐aroylbenzofurans; this route involves intermolecular double cyclocondensation of α‐sulfonyl o ‐hydroxyacetophenones with substituted α‐hydroxy arylketones and the formation of one carbon‐carbon double (C=C) bond and one carbon‐oxygen single (C−O) bond (green bonds, Scheme 1).…”
Section: Introductionmentioning
confidence: 99%